Rancang Bangun Alat Otomatis Pengganti dan Pengontrol Air dengan Deteksi Tingkat Kekeruhan dan PH Pada Akuarium Ikan Cupang - Sitio, Sartika Lina Mulani; Nardiono; Samudra, Yuda (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
Water quality that is not optimally maintained can have a negative impact on the health of ornamental fish, especially Bluerim betta fish that require an aquarium environment with a certain level of acidity and turbidity of the water. The problems that are often faced by ornamental fish hobbyists are delays in changing water and difficulties in monitoring water conditions manually. This study aims to design and build an automatic water replacement and control system in betta fish aquariums with the ability to detect turbidity levels and water pH in real-time. The system uses a pH-SEN0161 sensor to measure acidity, a turbidity-SEN0189 sensor to detect turbidity in NTU units, and an SRF05 ultrasonic sensor to measure water level. The software was developed using the Arduino IDE and implemented on the Arduino ATMega2560 microcontroller as well as the NodeMCU ESP8266 for data processing and automatic control. The test was carried out for 30 days with an ideal pH standard between 6–7 and a turbidity value below 400 NTU. The test results show that the system can work optimally in replacing and controlling the water conditions of the Bluerim betta fish aquarium, thus supporting the quality of life of the fish effectively and efficiently.